2020
DOI: 10.7759/cureus.10894
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Based Prevalence of Iron Deficiency Anemia among Pre-School Children in Dubai

Abstract: Introduction: Iron deficiency anemia (IDA) is an internationally recognized leading cause of disability and contributes to childhood morbidity and mortality. The prevalence of IDA is higher in developing countries, especially in Arab countries, compared to the west. Methods: To assess the prevalence of IDA, we analyzed the data of children aged between one to five years seen at Dr. Sulaiman Al-Habib Medical Group's tertiary care hospital in Dubai, United Arab Emirates (UAE) from 2016 to 2018. Results: We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Two studies indicated the prevalence of iron deficiency anemia in children under five years of age. The first study, conducted in 2019 with 259 infants in the Hatta suburb in the UAE, found that 22% of the infants were anemic [ 86 ], while the second study conducted by Faysial et al found that the prevalence of anemia was 31% of hospitalized cases that were diagnosed as iron deficiency anemia in Dubai [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies indicated the prevalence of iron deficiency anemia in children under five years of age. The first study, conducted in 2019 with 259 infants in the Hatta suburb in the UAE, found that 22% of the infants were anemic [ 86 ], while the second study conducted by Faysial et al found that the prevalence of anemia was 31% of hospitalized cases that were diagnosed as iron deficiency anemia in Dubai [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 28 articles were included. Out of 28 articles, 13 were done in the Asian continent, 5 , 24 - 35 7 were done in the African continent, 36 - 42 3 in the North-America continent, 43 - 45 1 in South-America, 46 and 4 were done in the European continent. 47 - 50 The sample size of included study varied from 23 36 to 7138 30 under-5 children.…”
Section: Resultsmentioning
confidence: 99%
“…The minimum prevalence of IDA (1.1%) was reported in North America 44 and the maximum prevalence of IDA (33.2%) was reported in Pakistan, Asia. 24 Four studies 5 , 34 , 35 , 46 only report factors that are associated with IDA and ID. The included articles’ detailed features for meta-analysis were given in detail in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This significantly lower prevalence of IDA in the current study could be attributed to the overall improvement in dietary conditions in Saudi Arabia including adequate and sufficient micronutrients intake in addition to increased food fortification programs. [12] While in a study conducted by Faysal et al [13], more male children were affected by IDA than females.…”
Section: Fig 2 Prevalence Of Anemia In Preschool Childrenmentioning
confidence: 99%